Baseline pulmonary hypertension in heart transplant recipients: 9 years of experience at Almazov National Medical Research Centre - M. A. Simonenko; G. V. Nikolayev; K. N. Malikov; P. A. Fedotov; Y. V. Sazonova; M. A. Bortsova; V. E. Rubinchik; A. O. Marichev; A. E. Bautin; M. Y. Sitnikova; M. L. Gordeev; M. A. Karpenko (Вестник трансплантологии и искусственных органов, 2020)
Objective: to assess the impact of baseline pulmonary hypertension (PH) on early and long-term outcomes following heart transplantation (HT). Materials and methods. From January 2010 to December 2018, 112 HTs were carried out. Based on right heart catheterization results, all recipients were divided into 2 groups: Group 1 with PH (n = 76; mean pulmonary arterial pressure (mPAP) ≥25 mm Hg), Group 2 – without PH (n = 36; MPAP <25 mm Hg). The average age of Group 1 patients was 46.4 ± 14.9 years, baseline pulmonary vascular resistance (PVR) was 3.5 ± 1.5 Wood units, PVR after reversion test (nitric oxide – 80 ppm, iloprost 20 μg) – 2.8 ± 1.0 Wood units, systolic PAP (sPAP) – 50.1 ± 13.4 mm Hg. The average age in Group 2 was 47.3 ± 12.2 years, baseline PVR – 2.1 ± 0.8 Wood units, sPAP – 27.4 ± 5.3 mm Hg. The dynamics in indicators of early postoperative period (duration of mechanical ventilatory support, use of vasodilators and inotropic support and the length of stay in intensive care unit (ICU), 30-day mortality) and long-term post-HT echocardiography results were assessed. Results. Due to acute right-ventricular failure (RVF) developing after heart transplantation, veno-arterial extracorporeal membrane oxygenation (VA-ECMO) was done in 8 patients (11%) from Group 1 and one patient (3%) from Group 2. Presence of PH did not affect duration of mechanical ventilatory support, inotropic support, and length of stay in ICU. Levosimendan therapy in the early postoperative period was more often performed in Group 1 (n = 29) than in Group 2 (n = 6) (p = 0.048). Nitric oxide inhalation was also more often administered in Group 1 (n = 54); Group 2 (n = 7), (p = 0.003). Sildenafil therapy after HT was comparable in both groups Group 1 (n = 25); Group 2 (n = 6), (p = 0.048). In early post-HT stages, 14 patients died, 30-day mortality was comparable in both groups (p = 0.12). Six months after HT, no differences were found in the sPAP (p = 0.21) and PVR (p = 0.07) levels. Conclusion. Patients with baseline PH after HT have a more severe early postoperative period, including a higher RVF incidence, with the need for ECMO implantation. A PVR level >3.5 Wood units is not a threshold for HT. Patients with baseline PVR >3.5 Wood units following HT show comparable results with patients without baseline PH. This allows such patients (baseline PVR >3.5 Wood units) to be considered for inclusion in the heart transplant waiting list. In addition, 30-day mortality and duration of mechanical ventilatory support after HT in patients with and without baseline PH did not differ. Regardless of the baseline level of sPAP and PVR, all patients showed improvement in these parameters after HT. Six months after HT, no differences were found in sPAP and PVR levels in the patients, regardless of whether there was baseline PH or not.